Factores de riesgo y su incidencia en la disminución de agudeza visual en adolecentes del octavo de básica Unidad Educativa Darío C Guevara, Babahoyo Los Ríos periodo mayo septiembre 2019 - Ocampo Espín, Cristian Robinson (2019)
Introduction: The visual health system is an extremely effective means for the rapid assimilation of environmental information that helps guide behavior; Therefore, sight is the most important sense for learning, memory and interaction with the environment. Objective: To determine the relationship of the Risk Factors and the decrease in visual acuity in adolescents of the eighth basic educational unit "Darío C Guevara" Babahoyo los Ríos period May September 2019. Methodology: A quantitative methodology was carried out, and an observational and prospective analytical study. The study population included 63 students, between 11 and 13 years of age, following the scheme of inclusion and exclusion criteria. Results: The reduced population included an adolescent from 11 to 13 years of age, the predominant sex in this study was female, the degree of decrease in predominant visual acuity was moderate, that is, a measure of 20/30 to 20 / 40, The most prevalent refractive errors in ascending order were: myopia, farsightedness, astigmatism, myopia prevailing with 50%. Conclusion: The most prevalent diseases identified in this study were myopia, physiological, personal and social factors were influential characteristics in the decrease of the visual acuity of adolescents, in relation to age it was 11 to 12 years, sex predominated female with 56%.